Disrupted distance learning: the impact of Covid-19 on study habits of distance learning university students. (2nd September 2021) - Aristeidou, Maria; Cross, Simon
ABSTRACT: Despite a growing body of work on understanding how students perceived the impacts of the Covid-19 pandemic, the effects on existing distance learning universities have received less attention. This study aimed to understand changes in distance learning students' study habits (learning, assessment and social activities) and assess the factors associated with negative impacts. An online survey collected information on demographics, study-related information, Covid-19 personal circumstances and changes in study habits from 555 undergraduate students at The Open University, UK. Of the study population, an average of 36% reported negative impacts on their study activities and 15% positive impacts. Logistic regression analysis (n = 269) demonstrated that negative impacts on study habits overall were associated with difficulties in managing workload and limited interaction with other students. Other factors, such as socioeconomic background, study level, limited interaction with tutors, age, personal health, employment issues, and childcare and caring responsibilities, relate to particular study habits. Our findings have implications for how universities with new and existing distance learning practices address these factors and better support ongoing learning activity during Covid-19 and other similar disruptions.